“Mitolinguagem” como Forma do Saber em Darcy Ribeiro - Bianka de Andrade Silva (2022)
From the end of the 19th century, the reactivation of mythical knowledge and the consequent revaluation of the form of thinking became common. Throughout the 20th century, it became difficult to sustain the theory of the dichotomy between myth and logos, besides its statement in the name of overcoming it, despite the demythologizing efforts. Therefore, faced with this phenomenon of emancipation through the mythical thought passed, which opposes and denounces the supposed autonomy of man through Cartesian reason, some thinkers such as Lévi-Strauss, Eduardo Viveiros de Castro, and Darcy Ribeiro value indigenous myths, whereas others, such as Walter Benjamin and Roger Caillois, uncover new civilization myths under the spotlight of reason. To explain the remythologizing ascension, we will focus on Darcy Ribeiro, a studious of the Brazilian indigenous population, and one of Lévi-Strauss's research sources, known as a distinguished voice of the damage caused by (post-) colonialism with its exploratory and logocentric principles. In the context of these new myths and based mainly on the contributions of Ernst Cassirer, Hans Blumenberg, Roger Caillois, and Lévi-Strauss, we propose the notion of “mytholanguage”.